1991
DOI: 10.1002/ijc.2910470526
|View full text |Cite
|
Sign up to set email alerts
|

Role of the extracellular matrix on the growth and differentiated phenotype of murine colonic adenocarcinoma cells in vitro

Abstract: The growth and differentiation characteristics of MAC 15 murine adenocarcinoma cells, derived from routine passage in vivo for growth in vitro on a plastic substrate (MAC15j cells), were compared under conditions in which the cells were seeded onto a substrate of type-I collagen which was either attached to plastic or was released to float free in medium. Cells grown on a plastic substrate consisted of a heterogeneous, largely anaplastic population with a putative enterocytic morphology but with no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In the case of 2-D cell culture, contact between RTll2 cells and lens capsules markedly influenced the growth behaviour of these cells, while artificial supports hindered the epithelial morphogenesis and the development of the epithelial cell polarity. Confirming the findings of others [52,71] we can support the suggestion that the degree of morphological and physiological differentiation of epithelial cells is largely affected by the physical constitution of the substratum as well as by factors of their local environment [18,63]. In addition, more recent ihvestigations have demonstrated that ceils cultured on a natural kidney capsule revealed a morphology of the tight junctions almost identical to that of native cells while ceils grown on plastic or on collagen coatings expressed only an irregular pattern of junctional strands [33].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the case of 2-D cell culture, contact between RTll2 cells and lens capsules markedly influenced the growth behaviour of these cells, while artificial supports hindered the epithelial morphogenesis and the development of the epithelial cell polarity. Confirming the findings of others [52,71] we can support the suggestion that the degree of morphological and physiological differentiation of epithelial cells is largely affected by the physical constitution of the substratum as well as by factors of their local environment [18,63]. In addition, more recent ihvestigations have demonstrated that ceils cultured on a natural kidney capsule revealed a morphology of the tight junctions almost identical to that of native cells while ceils grown on plastic or on collagen coatings expressed only an irregular pattern of junctional strands [33].…”
Section: Discussionsupporting
confidence: 84%
“…When grown on solid substrata the cells are forced to feed completely from the apical side whereas permeable filters permit access of nutrients to both surfaces, thus promoting polarized growth of the cells [13,28,71]. The basal lamina and some of its individual components are important factors for the expression of the polarized phenotype of epithelial cells in vitro [40,54,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These had internal microvillous surfaces and content that was positive for all examined CEA subfamily antigens except CEACAM7. These cytoplasmic neostructures have been found in a variety epithelial neoplasm [39] and cancer cell lines, including HT‐29 cells [57, 58]. It is believed that, in epithelial cells, the appearance of the intracellular lumina is connected with a dysfunction of the Golgi complex caused by the loss of cell polarity in cases of malignancy or cell isolation.…”
Section: Discussionmentioning
confidence: 99%